The Effect Of The Implementation Of The Iso 9001:2015 Quality Management System On Product Quality In The Production Department Of Pt Sentralindo Teguh Gemilang - SOBALI, UTEP; Windy Pressa; Badriyah (ASIAN PUBLISHER, 2024)
This study aims to analyze the effect of the implementation of the ISO 9001:2015 quality management system on Product Quality in the Production Department of PT. Sentralindo Teguh Gemilang. This research method uses a quantitative method with a non-probability sampling technique using a simple random sampling technique. Data was collected by questionnaires distributed using google forms to employees of the production department of PT. Sentralindo Teguh Gemilang. The collected data was analyzed using a simple linear regression method to test the relationship between the variables of quality management system implementation and product quality. The results of this study are that the implementation of the quality management system and product quality has a positive influence with the beta coefficient showing a positive 0.378, the remaining 61.7% is influenced by other variables that are not included in the research model. The results of the analysis are expected to be used as a reference to strengthen and improve the implementation of the ISO 9001:2015 Quality Management System through careful monitoring and continuous adjustment to factors that support quality improvement and for researchers it is recommended to conduct a more in-depth study to identify and analyze other factors that affect product quality in the company and it is recommended to conduct analysis on other objects.